New constraints on granulite facies metamorphism and melt production in the Lewisian Complex, northwest Scotland - Feisel, Y; White, RW; Palin, RM; Johnson, TE (Wiley, 2018)
In this study, we investigate the metamorphic history of the Assynt and Gruinard blocks of the Archean Lewisian Complex, northwest Scotland, which are considered by some to represent discrete crustal terranes. For samples of mafic and intermediate rocks, phase diagrams were constructed in the Na2O–CaO–K2O–FeO–MgO–Al2O3–SiO2–H2O–TiO2–O2 (NCKFMASHTO) system using whole-rock compositions. Our results indicate that all samples equilibrated at similar peak metamorphic conditions of ~8–10 kbar and ~900–1,000°C, consistent with field evidence for in situ partial melting and the classic interpretation of the central region of the Lewisian Complex as representing a single crustal block. Melt-reintegration modelling was employed in order to estimate probable protolith compositions. Phase equilibria calculated for these modelled undepleted precursors match well with those determined for a subsolidus amphibolite from Gairloch in the southern region of the Lewisian Complex. Both subsolidus lithologies exhibit similar phase relations and potential melt fertility, with both expected to produce orthopyroxene-bearing hornblende granulites, with or without garnet, at the conditions inferred for the Badcallian metamorphic peak. For fully hydrated protoliths, prograde melting is predicted to first occur at ~620°C and ~9.5 kbar, with up to 45% partial melt predicted to form at peak conditions in a closed-system environment. Partial melts calculated for both compositions between 610 and 1,050°C are mostly trondhjemitic. Although the melt-reintegrated granulite is predicted to produce more potassic (granitic) melts at ~700–900°C, the modelled melts are consistent with the measured compositions of felsic sheets from the central region Lewisian Complex.